Transformation of Islamic Values through Integrative Learning Strategies: A Phenomenological Study at Islamic Elementary School in Lampung - Munawaroh Munawaroh; Kholid Musadad; Akhmad Khoiri; Ahmad Abdillah (Pedagogik Journal of Islamic Elementary School, 2026)
Instilling Islamic values ​​in elementary school students still faces challenges because learning tends to focus on cognitive aspects rather than the transformation of values ​​that shape students' characters. This study aims to analyze the transformation of Islamic values ​​through teacher learning strategies in elementary school students. The study used a qualitative phenomenological approach with data collection techniques in the form of semi-structured interviews, participatory observation, and documentation. Participants consisted of school principals, Islamic Religious Education teachers, class teachers, and students who were selected purposively. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that: (1) the transformation of Islamic values ​​is supported by the school's commitment to building a religious culture; (2) learning strategies in the form of role models, habituation, self-reflection, contextual discussions, and reinforcement of positive behavior help internalize Islamic values; (3) the integration of Islamic values ​​in various subjects makes learning more meaningful and contextual; and (4) there are changes in student behavior shown through increased religious attitudes, honesty, discipline, responsibility, and social awareness. This study concludes that integrative and experience-based learning strategies are effective in transforming Islamic values ​​and strengthening the formation of students' religious character in elementary schools.